Evento tromboembólico em neonato de mãe com COVID-19 - Mariana Gaspar Mendonça; Anelise Steglich Souto; Mônica Akemi de Souza dos Reis (Residência Pediátrica, 2023)
INTRODUCTION: Premature birth is one of the main perinatal complications of maternal SARS-CoV-2 infection. CASE REPORT: Premature newborn, the daughter of a mother with a severe condition of COVID-19, who presented a thromboembolic event on the first day of life and evolved with hypoxic-ischemic encephalopathy. DISCUSSION: Investigation was carried out on the cause of the framework, management with enoxaparin and curative with collagenase, even though it was not possible to avoid the loss of the auricular region. Immunohistochemical evidence of Spike-19 protein was found in the fetal placental part. RT-PCR tests for SARS-CoV-2 without oropharyngeal swab were negative. A maternal coronavirus infection should be included in any differential diagnosis as a cause of a thromboembolic event in the neonatal period.